Synthesis and structural characterization of CoxFe3−xC (0 ≤ x ≤ 0.3) magnetic nanoparticles for biomedical applications - Gangwar A.; Singh G.; Shaw S.K.; Mandal R.K.; Sharma A.; Meena S.S.; Prajapat C.L.; Prasad N.K. (My University, 2025)
Herein, cobalt-substituted iron carbide (CoxFe3−xC, 0 ≤ x ≤ 0.3) magnetic nanoparticles (15-30 nm) were prepared by a sol-gel assisted route. X-ray diffraction (XRD) and electron diffraction patterns suggested that all the samples had a single phase structure. Furthermore, Mössbauer spectroscopy validated the monophasic nature of all the Co-substituted iron carbides, except for x = 0.3. The results of Mössbauer spectroscopy for this sample indicated the presence of the Fe-Co alloy along with the carbide phase. The saturation magnetization value was found to decrease with an increase in Co concentration (x ≤ 0.16); however, it increased for the x = 0.3 sample due to the presence of a secondary phase (Fe-Co alloy). Ferrofluids of the pure and Co-substituted iron carbides in oleic acid exhibited good heating abilities during the magnetic hyperthermia experiment at different external fields. © The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.